Managing an outpatient parenteral antibiotic therapy team: challenges and solutions - Halilovic, Jenana (Dove Medical Press, 2014)
Outpatient parenteral antimicrobial therapy (OPAT) programs should strive to deliver safe, cost effective, and high quality care. One of the keys to developing and sustaining a high quality OPAT program is to understand the common challenges or barriers to OPAT delivery. We review the most common challenges to starting and managing an OPAT program and give practical advice on addressing these issues.